2017
DOI: 10.3390/sym9030028
|View full text |Cite
|
Sign up to set email alerts
|

On the Legibility of Mirror-Reflected and Rotated Text

Abstract: Abstract:We happened to observe that text that was reflected about either the horizontal or vertical axis was more difficult to read than text that was reflected about first one and then the other, which amounts to a 180-degree rotation. In this article, we review a number of studies that examine the nature of recognizing reflected and inverted letters, and the frequency of mirror reversal errors (e.g., confusing 'b' for 'd') in children and adults. We explore recent ideas linking the acquisition of literacy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 181 publications
0
6
0
Order By: Relevance
“…However, the estimation of the frequency of rotations is rare in the literature. An analogous absence was pointed by Erlikhman, Strother, Barzakov, and Caplovitz (2017). They noted that, since the work by Kolers and coworkers in the 60s or 70s (e.g.…”
Section: Discussionmentioning
confidence: 64%
“…However, the estimation of the frequency of rotations is rare in the literature. An analogous absence was pointed by Erlikhman, Strother, Barzakov, and Caplovitz (2017). They noted that, since the work by Kolers and coworkers in the 60s or 70s (e.g.…”
Section: Discussionmentioning
confidence: 64%
“…However, it has been long appreciated that what we perceive is determined not only by the physical properties of the current input, but also by our perceptual history. For example, consider how much harder it is to read upside-down text [6] or to match a stranger's vs. a friend's photograph to their actual face [7]. Such effects of prior experience on perception can be observed not only for arguably "higher-level" processes such as recognition, but also for "lower-level" processes such as amodal completion [8], computing shape from motion [9], and computing 3-dimensional structure from object contours [10] and binocular disparity [11].…”
Section: Language As a Form Of Experience That Affects Perceptionmentioning
confidence: 99%
“…It has been shown that the spontaneous inclination to identify an image as the same, regardless of its left-right orientation (a phenomenon known as "mirror invariance" or "mirror generalization"), is inhibited by literacy. While mirror generalization is spontaneously found in infants (for a review, see [88]), in a same-different task involving mirror-reflected pairs, literate adults familiar with the Latin alphabet found it difficult to answer "same" to mirror-reversed stimuli than illiterate adults [89][90][91]. This has been explained in terms of the acquisition of a written system that incorporates mirrored letters (e.g., b and d), in the sense that this enhances sensitivity in the discrimination of lateral mirror-images (see also [92]).…”
Section: Potential Impact and Limitations Of The Studymentioning
confidence: 99%